(untitled) (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The study aimed to identify the opportunities and challenges in the development of Integrated Reporting based on the principles of dialogic accounting and to analyze the elements related to engagement with stakeholders. An analogy was made between the principles of dialogic accounting and integrated reporting and a content analysis in the reports evidenced by the Banco Nacional de Desenvolvimento, referring to the years 2018 to 2020. The following opportunities were identified: engagement with stakeholders, provision of accounts and transparency and improved dialogue. And as challenges: understanding the content. Furthermore, it was understood that the bank appreciates the engagement with its stakeholders and presents non-financial information providing a scenario for the development of dialogic accounting and integrated reporting.